AW-OZ: a Novel Approach to Explosion Risk Assessment of Equipment and Process Nodes used for Processing Bulk Materials Containing Combustible and Explosive Dusts - Andrzej Wolff; Zbigniew Wolff; Sebastian Slaboszewski (Chemical Engineering Transactions)
Following many years of work in the area of explosion and process safety and the explosion risk assessments carried out for process installations in a number of industries, it was determined that there was a need to develop a new approach to risk/hazard assessment based fundamentally on process data. The objective of the work carried out was to reduce the role of subjective assessment, which characterizes the commonly used PHA (Preliminary Hazard Analysis) method. This resulted in the development of the AW-OZ methodology for quantitative hazard level assessment. It is applicable to the evaluation of typical equipment used in industry to process bulk substances that contain combustible and explosive dusts. Determining the risk value associated with the operation of the equipment allows, in the next step of the procedure, a qualitative assessment of the probability / frequency of ignition source activation and the possible consequences of an explosion using VDI approach (VDI 2263-6, 2017). The advantage of AW-OZ approach is the quantitative assessment of the level of hazard/risk associated with equipment operation and also the compliance with the provisions of ATEX User (Directive 1999/92/EC) for explosion risk assessment. Relying on reliable process data reduces the risk of taking up wrong decisions.